The Effect Of The Gap Between Rate Sensitive Assets (Rsa) And Rate Sensitive Liability (Rsl) And Changes In Interest Rates Gives Implications For Net Interest Income - Tatang Suhidayat; Riwandari Juniasti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
In management Asset Liability Management (ALMA), banks can try look for road best in avoid possibility big loss as consequence from happening changes on level ethnic group bank interest, inflation as well as changes on mark swap a currency. Analysis in gap management also aims to go as far Possible release the bank from possibility happening mismatch caused it No liquid as well as No can fulfil his obligations party third. Method used in study This is descriptive analysis with approach studies case (case study) on the People's Precredit Bank. Research results showing partially the variables that can form net interest income are influenced by gap positions and interest rates. Then from the regression equation and the results of the t test, it means that the formation of net interest income that occurs in the company is influenced by a positive gap position (RSA RSL) and a decrease in interest rates with a calculation system with changing interest rates (floting rate).